Specialization and niche overlap across spatial scales: Revealing ecological factors shaping species richness and coexistence in Australian songbirds - Harmáčková, Lenka; Remešová, Eva; Remeš, Vladimír (The Journal of animal ecology, 2019)
Ecological specialization enables the partitioning of resources and thus can facilitate the coexistence of species and promote higher species richness. Specialization and niche partitioning are expected to exert a decisive influence on local spatial scales, while species richness at regional scales should be shaped mostly by historical factors and abiotic conditions. Moreover, specialization is expected to be particularly important in communities that are exceptionally species rich for their environmental conditions. Concurrently, niche overlap in these communities should be minimized to enable species coexistence. We tested these hypotheses by studying specialization-richness relationship and niche overlap in assemblages of 298 species of songbirds (Passeriformes) across Australia. We used local (2-6 ha) to regional (bioregions) spatial scales and detailed data on habitat, diet and foraging behaviour (method, substrate and stratum). We expected the richness-specialization relationship to be particularly strong (a) on local spatial scales and (b) in communities exceptionally species rich for given environmental conditions (approximated by moisture and vegetation complexity). We also expected (c) low niche overlap in assemblages with specialized species. Only the third prediction was partly supported. First, while the specialization and species richness were often positively related, the strength and the direction of the relationship changed between traits and across spatial scales. The strength of the specialization-richness relationship was consistently positive only in foraging stratum, and it increased towards smaller spatial scales only in case of habitat and diet. Simultaneously, species in local communities demonstrated high overlap in habitat and diet. Second, we did not find particularly strong specialization-richness relationships in exceptionally species-rich communities. Third, we found the expected negative relationship between specialization and overlap in foraging stratum and substrate (in local communities), suggesting that species partition ecological space locally in terms of where they find food. Our expectations were only weakly supported. Specialization on foraging stratum was probably important in facilitating species coexistence. Conversely, although species were often specialized on habitat and diet, high overlap in these traits did not preclude their local coexistence. Overall, specialization and overlap in foraging traits were more important for species coexistence than habitat or diet.
Keywords: community assembly; niche partitioning; Australia; passeriformes; Austrálie; zvířata; ekosystém; zpěvní ptáci; Ecosystem; Ecology; ekologie; null models; Songbirds; spatial scales; Animals